The Association between Short Periods of Everyday Life Activities and Affective States: A Replication Study Using Ambulatory Assessment - Bossmann, Thomas; Kanning, Martina; Koudela, Susanne; Hey, Stefan; Ebner-Priemer, Ulrich W. (Frontiers in Psychology, 2013)
Regularly conducted exercise programs effectively influence affective states. Studies suggest that this is also true for short bouts of physical activity of ten minutes or less. Accordingly, everyday life activities of short duration might be used to regulate affective states. However, this association has rarely been studied in reference to unstructured activities in ongoing real-life situations. The current study examined the influence of various everyday life activities on three dimensions of mood (valence, calmness, energetic arousal) in a predominantly inactive sample. Ambulatory Assessment (AA) was used to investigate the association between actual physical activity (aPA) and affective states during the course of one day. Seventy-seven students ages 19 - 30 participated in the study. aPA was assessed with accelerometers, and affective state assessments were conducted hourly using an e-diary with a six-item mood scale that was specially designed for AA. Multilevel analyses indicated that the mood dimensions energetic arousal (p = .001) and valence (p = .005) were positively influenced by the intensity of the activity carried out in the ten minutes prior to the assessment. As their activity increased, the participants’ positive feelings and energetic arousal increased. However, the students’ calmness was not affected by their activity levels. The findings highlight the importance of integrating short activity intervals of 10 minutes or less into everyday life routines to improve affective states.